Formações iniciais e continuadas e seus reflexos no discurso sobre a concepção de língua e sobre a prática de ensino de professores alfabetizadores participantes do PNAIC - Farias, Andréa Tôrres Vilar de (2020)
This qualitative thesis analyzes the language conception of the Alphabetization Cycle teacher who is part of PNAIC through his discourse on classroom practice in Portuguese Language classes. For this, we conducted interviews through semi-structured questionnaires with six teachers the municipalities of Campina Grande-PB and Queimadas-PB. The general objective of this research is to understand which language conceptions and which possible teaching practices the teachers of the Alphabetization, participants in the PNAIC training, base themselves on teaching, seeking to understand how teachers who are pedagogues, who do not have specific language training, but who undergo continuous training, work the student's language training. For this, we set specific objectives that aimed to discuss the teaching of the Portuguese language based on the assumptions of the PCN and PNAIC; observe what knowledge that articulates about the Portuguese Language among the literacy teachers, identifying the language image that matters when literacy, as well as what is taught about the language, how and for what; to ascertain, through the analysis of the teachers' statements, if their practices, during the Alphabetization Cycle are implemented according to the guidelines of the official documents and PNAIC's continuing education, which guide the practice of Portuguese Language teaching in Brazil; If the practices are closer to the curriculum of the Pedagogy course or to the guidance received in the trainings, that is, which course offers them the most support and is reflected in the conceptions of language teaching of the alphabetization teachers and their practices. The survey results show that most of the teachers interviewed, even attending government training programs aimed at improving the teaching and learning process, do not have a basis in language knowledge that favors more consistent work. Most of the time, they fail to put into practice what they learn in training, presenting great difficulty related to language teaching, because they are facing a mismatch between theory and practice and a lack of clarity about the goal and conception of language adopted by they. In some situations they present a more centralized language work in Traditional Grammar (GT); In others, there is a mixture: text / grammar, or grammar in the text, emphasizing a practice that gives priority to the transfer of content in a fragmented and decontextualized way, making the proposal of language teaching, through the actual practice of use, is not so present in the practices adopted in schools, and is mostly summarized in a teaching of metalanguage. Keywords: Linguistic Policy; Teacher Training; Language Conception; PNAIC; Alphabetization Cycle.